[RETRACTED] Short-term dynamics and growth parameters of cyanobacteria and microcystins in freshwater from the Sidi-Yacoub dam, North-east of Algeria - ZINE EDDINE BOUDJELLAB; MAYA GHANNAM; NADJELA CHAIB; ZOHRA CHEKROUD (Society for Indonesian Biodiversity, 2023)
Abstract. Boudjellab ZE, Ghannam M, Chaib N, Chekroud Z. 2023. Short-term dynamics and growth parameters of cyanobacteria and microcystins in freshwater from the Sidi-Yacoub dam, North-east of Algeria. Biodiversitas 24: 5598-5609. The study aimed to establish the inventory of the blue-green algae species and monitoring the monthly evolution of their specific and total cell biovolume in Sidi-Yacoub dam, located northwest of Algeria from February 2021 to January 2022. At the same time, a monthly assessment of particulate and dissolved microcystin concentrations, chlorophyll pigment concentrations, and certain physicochemical parameters has been conducted. Eight species were listed, cited in descending order of their average relative abundance are: Microcystis aeruginosa (54.05%); Oscillatoria limosa (23.68%); Merismopedia sp. (8.34%); Anabaena cylindrica (3.53%); Aphanizomenon sp. (2.41%); Microcystis botrys (2.66%); Woronichinia sp. (2.95%) and Chroococcus limneticus (2.34%). The maximum value of the total biovolume, was recorded during December (27.4x106 µm3.L-1). The maximum concentration of chlorophyll-a and phycocyanin were respectively 55.26 and 47.46 µg L-1, recorded in September 2021. The microcystins detected where mainly in the cell-bound form, reaching a maximum concentration of 0.134 µg L-1 in October 2021. The principal component analysis shows a strong positive correlation between the total monthly cell biovolume, particulate microcystin (MCP) and some physicochemical parameters. M. aeruginosa has been identified as the primary producer of microcystins found in the eutrophic waters of the dam, with these microcystins being predominantly maintained in an intracellular form throughout most of the year.